Seedling And Adult Plant Resistance To Stripe Rust In Uttarakhand Landraces Of Wheat (Applied Biological Research, 2018)
In present study, twenty-six landraces of wheat collected from different  parts of Uttarakhand (India) were tested for stripe rust resistance. Initially,  field resistance test was carried out at two locations, namely Hawalbagh and  Dalang-Maidan (India), during 2013-14 and 2014-15 under natural  conditions. The landraces were also tested against 3 pathotypes of stripe  rust pathogen (110S119, 46S119 and 78S84) at seedling and adult plant  stage under controlled conditions. In field, 13 landraces were found highly  resistant, of which 8 were immune. The remaining 13 landraces showed  varying levels of partial resistance and expressed significant genotype x  environment interactions. Of the 26 landraces, only one landrace (VHC  6285) was immune against all the three pathotypes both at seedling and  adult plant stages. Five landraces (VHC(BD)2, VAH-CW 3166, VRB-CW 2106, VHC 6178 and VHC 6185) showed seedling resistance against 78S84,  and adult plant resistance (APR) against 110S119 and 46S119. Some  landraces showed both seedling and adult plant resistance against 46S119  and 78S84. Thus, apart from reporting new sources of resistance against  existing pathotypes, the current study seems to be first to report resistance  sources (both seedling and APR) against new pathotype 110S119.
Keywords: Landraces; pathotypes; stripe rust; Uttarakhand; wheat